Effect of Wood Preservatives on Surface Properties of Coated Wood - Turgay Ozdemir; Ali Temiz; Ismail Aydin (Advances in Materials Science and Engineering)
Effect of wood preservatives (waterborne and organicborne) on the performance of surface finishing properties is investigated. Sapwood of scots pine, (Pinus sylvestris L.), oriental beech (Fagus orientalis Lipsky), and chestnut (Castanea sativa Mill.) specimens (300 × 100 × 15 mm along the grain) were impregnated with aqueous solution of 2% CCA, 2% Tanalith E, 1% boric acid, and Immersol aqua. Surface roughness, dry film thickness, adhesion strength, gloss measurement, scratch, and abrasion resistance were determined according to related standards for treated and untreated samples. The results indicated that surface roughness and adhesion strength depended on wood species and the chemical composition of preservatives. Generally, waterborne wood preservatives increased the surface roughness of wood while the organic-based wood preservatives decreased it. The organic-based wood preservatives decreased adhesion but they increased gloss value. Wood preservatives did not affect the scratch resistance which was found to depend on properties of the coating. All the wood preservatives increased abrasion resistance.